TANTANGAN DAN PELUANG IMPLEMENTASI KURIKULUM MERDEKA DI KOTA BITUNG - Goni, Agnes; Warouw, Witnny Stesia (DIKSAR : Jurnal Pendidikan Dasar, 2023)
The Merdeka Curriculum has been a major focus in the world of Indonesian education, particularly in the city of Bitung. The Merdeka Curriculum is one of the curriculum options established by the Minister of Education and Culture, Nadiem Anwar Makarim, as a continuation of the official prototype curriculum. In this curriculum, educational institutions are given the freedom to choose the curriculum they will use. There are three predetermined curriculum options: the 2013 Curriculum, the Emergency Curriculum, and the Merdeka Curriculum, which must be chosen by each educational institution. Bitung city is one of the cities in Indonesia that has chosen to implement the Merdeka Curriculum uniformly across all schools. Although initially implemented for pioneer schools, later schools chose the independent IKM route, but starting from the second semester of the 2022/2023 academic year, all schools collectively use the Merdeka Curriculum for all phases/grades. By implementing this curriculum in all phases, from grades 1 to 6, it is hoped that students will become more active and independent in the learning process. However, like any other curriculum changes, the implementation of the Merdeka Curriculum also faces challenges, including teacher readiness, including teacher competence, infrastructure, and other related factors. This article will discuss the implementation of the Merdeka Curriculum using the literature review research method to provide a more comprehensive understanding of the implementation of the Merdeka Curriculum in terms of the challenges and opportunities it faces.